Zarządzanie wiedzą w klastrach - Stańczyk-Hugiet, Ewa (Knowledge Management in Clasters, 2006)
The main aim of this paper is to find answer considering on possibilities of developing knowledge in specific interorganisational net like cluster.First part of presented paper shows some meaning of knowledge processes. Secondly it is analyzed knowledge processes in one specific cluster.Concluding it can be said that regional cluster is the good place to develop knowledge processes especially in the field of product innovations which are encouraged by non- formal relations within cluster's partners.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 601-606